Short Review for Design and Implementation of a New Low-Cost Prototype Portable Smart Ventilator - Shereen Q. Blais; Jameel K. Abed; Mohannad J. Mnati; Tareq S. El-Hasan (Journal of Techniques)
This paper presents a set of research and an overview of the stages of development of the ventilator. The results of this research show how to produce a portable, smart, easy-to-manufacture and use device that can be developed at the lowest costs. Mechanical ventilation has become a lifesaver, especially during the outbreak of the Coronavirus COVID-19 where the patient needs continuous ventilation in order to help the respiratory system to perform its functions correctly due to the accumulation of fluid in the lungs resulting from viruses that infect the respiratory system, thus improving survival.